Environmental impact due to iron ore mining in Chhattisgarh - Das, Bhumika (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> Iron ore is an important mineral in Chhattisgarh. The production of iron ore is 5.50 million tones per year. Due to massive extraction of iron ore, it pollutes air, water and soil. When iron in solution reaches the water table it pollutes the ground water, while dissolved iron in surface water reacts with soil to cause soil erosion and effect the soil profile and sometimes minor particles of iron spread with air cause air pollution. Mining in Bailadila and Dalli-rajhra (Durg) have resulted into various environmental problems. Apart from these, the open cast mining which removes the top soil cover may invite occurrences of landslide. If the mining and industrial activities are carried out in an integrated planed way by continuous monitoring and taking effective mitigative measures in a timely manner then it will definitely prove to be economically beneficial in a sustainable manner. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>